Facebook as a public discourse platform: analysing online users’ language politeness (Conference on English Language Teaching, 2025)
This study investigates the implementation of politeness strategies within Facebook comment sections, guided by Brown and Levinson’s politeness theory (1987). As digital communication continues to thrive, Facebook serves as a prominent space where individuals from diverse backgrounds engage in conversations about social, political, and cultural issues. Using a descriptive qualitative method, this research examines how Indonesian users articulate their thoughts in response to controversial or debate-inducing public posts. The data comprise selected Facebook comments containing relevant opinions, emotional expressions, and language use. Employing pragmatic and discourse analysis, the research uncovers the presence of four politeness strategies: positive politeness, negative politeness, off-record, and bald on-record. These strategies represent various communication goals—from fostering solidarity to delivering critique. The analysis reveals that while many users strive to uphold politeness to maintain social balance, others opt for more straightforward or ironic expressions that defy conventional etiquette. Overall, this research underscores how language use in digital spaces mirrors broader cultural values, interpersonal dynamics, and user behavior, highlighting the importance of polite interaction in sustaining healthy online discourse.